The Intestinal Carriage of Plasmid-Mediated Colistin-Resistant Enterobacteriaceae in Tertiary Care Settings - Tkadlec, Jan; Kalova, Alzbeta; Brajerova, Marie; Gelbicova, Tereza; Karpiskova, Renata; Smelikova, Eva; Nyc, Otakar; Drevinek, Pavel; Krutova, Marcela (Antibiotics (Basel, Switzerland), 2021)
Background: In order to estimate the prevalence of plasmid borne colistin resistance and to characterize in detail the mcr-positive isolates, we carried out a sentinel testing survey on the intestinal carriage of plasmid-mediated colistin-resistant Enterobacteriaceae in hospitalized patients. Methods: Between June 2018 and September 2019, 1922 faecal samples from hospitalised patients were analysed by selective culture in presence of colistin (3.5 mg/L), and in parallel by direct detection of the mcr-1 to mcr-8 genes by qPCR. The mcr-positive isolates were characterised by whole-genome sequencing. Results: The prevalence of the mcr-1 gene was 0.21% (n = 4/1922); the mcr-2 to 8 genes were not detected. The mcr-1 gene was found to be localised in the IncX4 (n = 3) and IncHI2 (n = 1) plasmid type. One Escherichia coli isolate was susceptible to colistin due to the inactivation of the mcr-1 gene through the insertion of the IS2 element; however, the colistin resistance was inducible by culture in low concentrations of colistin. One human mcr-1 positive E. coli isolate was related genetically to the mcr-1 E. coli isolate derived from turkey meat of Czech origin. Conclusions:mcr-mediated colistin resistance currently poses little threat to patients hospitalised in Czech healthcare settings. The presence of the mcr-1 gene in the human population has a possible link to domestically produced, retail meat.
Keywords: Czech Republic; IncX4; E. coli; colistin; silent carriage; mcr